Pseudoaneurysm after carotid stenting: A case report and review of the literature - Ahmet Güner; Selçuk Pala; Sabahattin Gündüz; Şeyhmus Külahçıoğlu; Ezgi Gültekin Güner (KARE Publishing, 2020)
Carotid artery stenting has been a widely used interventional treatment method for the last 3 decades in the treatment of carotid artery stenosis. In the current literature, unlike major cardiovascular complications, less emphasis has been placed on carotid pseudoaneurysm (PA). A carotid artery PA can be caused by trauma, spontaneous infection, vasculitis, or it may be iatrogenic. However, the incidence of PA secondary to carotid stenting is extremely rare. Although it may be completely asymptomatic in rare instances, it usually progresses symptomatically (neck swelling, nerve compression, respiratory distress, hoarseness, dysphagia, and ischemic cerebrovascular events). Doppler ultrasound, contrast-enhanced computed tomography, and conventional angiography are the main diagnostic tools. Primary closure, including graft interposition, has been described as a surgical therapeutic option. An endovascular approach with placement of a covered or bare metal stent is an alternative treatment method to surgery.